The Effectiveness of Learning Using Short Story Writing Multiliteracy Model with Public Service Advertising Media Based on The Learning Types of Senior High School Students (Universitas Negeri Semarang, 2019)
Short story writing skills require the creativity of students. Students are required to be able to think creatively and be able to develop their imagination to produce interesting short stories. This study aims to determine the effectiveness of short story writing learning using multiliteracy models with public service advertising media based on the type of learning of senior high school students. The research design used was a quasi-experimental population of senior high school class XI students in the academic year 2019/2020. The research sample was taken using a purposive sampling technique. Data were collected using short story writing test techniques, non-tests conducted by observation, interviews, and documentation. Data were analyzed using the average similarity test (T-test) and analysis of variance (ANOVA). The results of this study can prove the effectiveness of the use of multi literation models with public service advertising media on learning to write short stories based on the learning type of senior high school students. The results of this study provide theoretical and practical advantages. Theoretically, this research can provide alternative theories of the use of innovative learning models that fit the needs of 21st -century students. The significance of this research for educators is the theory of innovative short story writing learning based on the type of student learning by using a multiliteracy model that utilizes public service advertising media.